2018
DOI: 10.4414/smw.2018.14594
|View full text |Cite
|
Sign up to set email alerts
|

Overuse of antimicrobial prophylaxis in low-risk patients undergoing transurethral resection of the prostate

Abstract: A low adherence to guidelines for low-risk patients undergoing TURP or PVP was reported. Given these preliminary data, there is an urgent need to monitor adherence to antimicrobial prophylaxis guidelines in urology to reduce antimicrobial resistance rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Unfortunately, the adherence to the EAU guidelines is not optimal. Antimicrobials are often used without a sound rationale, and evidence suggests that >50% of clinicians do not follow the guidelines for the use of antimicrobial agents [30] , [31] , [32] . The literature search outlined that there are several differences between EAU guidelines and American Urological Association/Canadian Urological Association/Society of Urodynamics, Female Pelvic Medicine & Urogenital Reconstruction guidelines, leading to contradictory and inconsistent recommendations [33] .…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Unfortunately, the adherence to the EAU guidelines is not optimal. Antimicrobials are often used without a sound rationale, and evidence suggests that >50% of clinicians do not follow the guidelines for the use of antimicrobial agents [30] , [31] , [32] . The literature search outlined that there are several differences between EAU guidelines and American Urological Association/Canadian Urological Association/Society of Urodynamics, Female Pelvic Medicine & Urogenital Reconstruction guidelines, leading to contradictory and inconsistent recommendations [33] .…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Preprocedural urine cultures were collected in 325 of 375 patients (86.7%) (Table 1). The most recent urine culture was performed a median (interquartile [IQR]) of 11 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) days before the procedure, and 106 of 325 patients (32.6%) had bacteriuria or candiduria. Management of preprocedural urine culture screening and treatment was considered inappropriate in 104 patients (27.7%).…”
Section: Manual Medical Record Review At Vha Sitesmentioning
confidence: 99%
“…6(p13) Surveys have demonstrated variability among urologists in their perceived adherence to the professional guidelines. 7,8 Few studies, however, have assessed whether antimicrobial prescribing behavior among urologists actually follows guideline recommendations. [9][10][11] Mossanen et al 10 used a large health care database to assess antimicrobial appropriateness in patients who had urologic procedures from 2007 to 2012.…”
Section: Introductionmentioning
confidence: 99%
“…In a preliminary study, we observed a non-adherence in TURP and GL to the recommended single-dose AP of more than 70% amongst urologists in Switzerland, Germany and Austria. AP in TURP and GL was regularly extended up to several days; the most common duration of AP was 2–3 days [8].…”
Section: Introductionmentioning
confidence: 99%